Samarium oxide as efficient and non-endangered metal for synthesis of sulfones from sulfides: an elemental sustainability concept - Wei Lam Wan; Preeyashenny A. Jagathison; Noor Fazira Mohd Fauzi; Onn Jew Lee; Poh Wai Chia; Su-Yin Kan (Journal of Taibah University for Science, 2023)
Oxidation of sulfide to sulfone is a fundamental process to produce many important pharmaceutical compounds. Formerly, efficient methods have been reported for the synthesis of sulfones from sulfides. Yet some limitations were identified, such as the unbalance use of metal catalysts and expensive oxidizing agent, low reaction yields and production of by-products. In this current research, oxidation of sulfides to sulfones is described in the presence of samarium oxide (Sm2O3) along with hydrogen peroxide. The SEM image showed the crystalline morphology of the Sm2O3 as a cubic single phase (ICSD 98-001-2948) with a size distribution between 120 and 300 nm. In the recyclability experiment, Sm2O3 catalyst can be reutilized for five successive cycles and afforded the desired end-products in great yields (97–95%). This current work is vital, as the usage of non-endangered metals in organic transformation is geared towards achieving the elemental sustainability concept.